A graphene-like semiconducting BC2P monolayer as a promising material for a Li-ion battery and CO2 adsorbent. Issue 3 (4th January 2023) - Fu, Xi; Cheng, Xiaoli; He, Chaozheng; Lin, Jian; Liao, Wenhu; Li, Liming; Guo, Jiyuan
Abstract : Herein, we reported a novel 2D BC2 P monolayer with great potential as an anode material for lithium-ion batteries which has the diffusion energies of 0.26 and 0.87 eV and high theoretical capacity of 1018.8 mA g h −1, and as the material for CO2 adsorption, respectively. Abstract : Searching for high-performance anode materials and CO2 adsorption materials are key factors for next-generation renewable energy technologies and mitigation of the greenhouse effect. Herein, we report a novel two-dimensional (2D) BC2 P monolayer with great potential as an anode material for lithium-ion batteries (LIBs) and as a material for CO2 adsorption. The adsorption energies of Li atoms and CO2 molecules on the BC2 P supercell are negative enough to assure stability and safety under operating conditions. More intriguingly, the BC2 P monolayer possesses a very high theoretical capacity of 1018.8 mA g h −1 for LIBs. In addition, the diffusion energy barriers of Li on the BC2 P supercell are 0.26 and 0.87 eV, showing good charge/discharge capability, and the electrode potential of Li is beneficial to their performance as an anode material. Moreover, four chemical and three physical adsorption sites were verified, indicating that the CO2 molecule was effectively adsorbed on the BC2 P supercell. These desirable properties make the BC2 P monolayer a promising 2D material for application in LIBs and for CO2 adsorbents aimed at highly efficient CO2 capture.